PREFERENCES OF MILLENIAL GENERATION CUSTOMERS IN CHOOSING ISLAMIC BANKS - Chairunnisa Buay Pemaca; Egi Arvian Firmansyah (STIESA Press, 2021)
The purpose of this study is to determine the preferences of customers in selecting Islamic Banks in Indonesia. This study uses a quantitative approach using Indonesian customers have accounts in Islamic Banks. Data were collected through a questionnaire and analyzed by Kruskal-Wallis Test Analysis. The number of respondents in this study is 200 persons. The results showed that the most preferred factor in selecting an Islamic bank is surprisingly not a religious factor. In fact, it is the comfort factors. The religious factor is in the second.